(untitled) (International Journal of Engineering and Computer Science, 2015)
As the number of security issues increased from day to day,we have to improve the security in efficient way.In the biometric signal based security system the major problems is to ensure the actual presence of real trait in contrast toa fake ,self-manufactured,synthetic,reconstructed traits.In this paper we propose a security lock system which provide security with combination of fingerprint,iris and palm images as biometric input.And we also include the authentication system for fake traits like silicon,playdoh,gelatin images by adding liveness assessment in a fast,userfriendly and non-intrusive manner through the image quality assessment method.In this paper we include 25 image quality features extracted from one image to differentiate the legitimate and impostor samples.Its suitable for real time security system in colleges,government sectors,private sectors,etc.This method is very efficient compared to previous state-of-the-art approaches.The cost of the method is very much reduced because the hardware is required to take the input only and the entire system is based on image processing software.The time consumption is also reduced as the recognition system is based on image processing software and we take only one image as input.And the security is very efficient as we take 25 different features in one images like MSE,NAE,AD,MD,etc.